Solid electrolyte and preparation method and application thereof
Through the use of compound I in solid electrolytes, the problem of hidden dangers and performance bottlenecks of traditional lithium -ion batteries was solved, and high -volume ion -conductivity, electrochemical stability, and electrode interface compatibility were realized, and the overall performance of solid -state batteries was improved.
Patent Information
- Application Number
- CN202411415252.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional liquid electrolyte lithium-ion batteries have safety hazards and performance bottlenecks. Solid electrolytes have challenges in the low room temperature ion conductivity, insufficient interface stability and strong corrosiveness of high polar solvents, which are difficult to meet the needs of high power density and long cycle life. .
Use compound I as a preparation raw material for solid electrolyte, the molecular structure design of the compound i to maintain the polarity, and at the same time introduce a functional group alky oxygen group that can form weakness with a variety of electrolyte ions, as a solvent to improve the electrolyte ion conductivity rate And electrochemical stability.
Through the application of compound I, the room temperature ion conductivity, electrochemical stability, and electrode interface of solid electrolytes are significantly improved, simplifying the preparation process and improving the overall performance of solid -state batteries.
Smart Images

Figure CN119381543A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to a solid electrolyte and a preparation method and application thereof. Background Art
[0002] With the miniaturization and lightweight of electronic devices and the rapid development of the new energy vehicle industry, the demand for high energy density and high safety rechargeable batteries is becoming increasingly urgent. Traditional liquid electrolyte lithium-ion batteries are difficult to meet future needs due to their potential safety hazards (such as flammability and leakage) and performance bottlenecks (such as energy density limitations). In this context, solid electrolytes have become the key direction to solve the above problems due to their excellent safety performance, wide electrochemical window and potential high energy density.
[0003] Solid electrolytes are mainly divided into three categories: inorganic solid electrolytes, polymer solid electrolytes and composite solid electrolytes. Among them, solid electrolytes have become a research hotspot due to their excellent mechanical strength, chemical stability and wide electrochemical window. However, solid electrolytes still face the following key challenges: (1) The ionic conductivity at room temperature is low (usually less than 10 -4 S / cm), which limits its performance in high power density applications; (2) the interface stability with the metal lithium anode is insufficient, which easily forms uneven lithium deposition and causes safety issues; (3) traditional solvents (such as N,N-dimethylacetamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO)) are highly polar and not only have strong corrosiveness to the lithium metal anode, but may also react with high nickel cathode materials (such as LiNi 0.9 Co 0.05 Mn 0.05 O2) and other adverse reactions will occur, affecting the cycle life and rate performance of the battery.
[0004] To solve these problems, researchers have proposed a variety of modification strategies: (1) adding ceramic fillers (such as Al2O3, TiO2, SiO2, etc.) to improve mechanical strength and ionic conductivity; (2) introducing ionic liquids as plasticizers to improve room temperature ionic conductivity; (3) constructing three-dimensional network structures, such as through cross-linking or electrospinning technology, to optimize ion transport channels. However, these methods often increase the complexity and cost of the preparation process, making it difficult to achieve large-scale industrial applications. In addition, some methods may introduce new interface problems or reduce the mechanical strength of the electrolyte. Summary of the invention
[0005] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a use of compound I in the preparation of a solid electrolyte.
[0006] A second object of the present invention is to provide a solvent for preparing a solid electrolyte.
[0007] A third object of the present invention is to provide a solid electrolyte.
[0008] A fourth object of the present invention is to provide a method for preparing the above-mentioned solid electrolyte.
[0009] A fifth object of the present invention is to provide a solid-state battery.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] The first aspect of the present invention provides the use of compound I in preparing a solid electrolyte. The structural formula of compound I is shown below:
[0012]
[0013] Wherein, X1, X2, and X3 are each independently selected from hydrogen, fluorine, chlorine, bromine, iodine, hydroxyl, amino or thiol, and X1, X2, and X3 are not hydrogen at the same time, and at most only one of X1, X2, and X3 is a hydroxyl, amino or thiol group; R1 and R2 are each independently selected from substituted or unsubstituted C1~C10 straight or branched alkyl, substituted or unsubstituted C3~C10 cycloalkyl, substituted or unsubstituted C1~C10 siloxane; wherein the substituted substituent includes at least one of fluorine, chlorine, bromine or iodine; the number of substitutions ranges from single substitution to full substitution.
[0014] The use of compound I according to the first aspect of the present invention in the preparation of a solid electrolyte has at least the following beneficial effects:
[0015] The present invention, through the design of molecular structure, makes compound I keep low polarity, while introducing functional group alkoxyl group that can form weak coordination with various electrolyte ions (such as lithium ions, sodium ions, potassium ions, etc.), realizes multiple optimization of compound performance, and this weak coordination helps to provide moderate solvation, while maintaining high mobility of ions, thereby optimizing the overall performance of electrolyte. Compound I has low polarity, can significantly reduce its corrosiveness to electrode materials, and can provide advantages to improve its compatibility with electrode materials, as well as compatibility with other preparation raw materials such as polymers, to form a uniform and stable solid electrolyte structure; and compound I has high chemical stability, which is conducive to achieving a wide electrochemical window; compound I is also conducive to promoting the dissociation of electrolyte salts such as lithium salts, thereby improving ionic conductivity; more importantly, compound I can form a stable local high-concentration solvent structure in the solid electrolyte, which is conducive to the rapid transmission of electrolyte ions, thereby improving the room temperature ionic conductivity of the solid electrolyte. It can be seen that the present invention can greatly improve the comprehensive performance of the solid-state electrolyte, including ionic conductivity, electrochemical stability and electrode interface compatibility, by introducing compound I, and is also conducive to simplifying the preparation process of the solid-state electrolyte, which provides important technical support for the development of a new generation of high-performance solid-state electrolytes and solid-state batteries, and is expected to promote the further development of electrochemical energy storage technology.
[0016] In some embodiments of the present invention, compound I is selected from compound A shown below:
[0017]
[0018] In some specific embodiments of the present invention, Compound I is used as a solvent for preparing a solid electrolyte.
[0019] The second aspect of the present invention provides a solvent for preparing a solid electrolyte, comprising the compound I in the application described in the first aspect of the present invention.
[0020] The solvent according to the second aspect of the present invention has at least the following beneficial effects:
[0021] When compound I is used as a solvent for preparing solid electrolytes, due to its low polarity, it is beneficial to improve the electrochemical stability and electrode interface compatibility of the solid electrolyte structure, and its alkoxy group can weakly coordinate with electrolyte ions (such as lithium ions, etc.), promote the dissociation of electrolyte salts, thereby improving the ionic conductivity of the solid electrolyte. Therefore, using compound I as a solvent for preparing solid electrolytes is conducive to obtaining high-performance solid electrolytes and solid-state batteries.
[0022] The third aspect of the present invention provides a solid electrolyte, comprising the following preparation raw materials: a polymer, an electrolyte salt, and the solvent described in the second aspect of the present invention; the polymer comprises at least one of a fluorinated polymer, a polyolefin polymer, a polynitrile polymer, a polyether polymer, a polyester polymer, a polyacrylate polymer, a chlorine-containing polymer or a polysiloxane polymer.
[0023] The solid electrolyte according to the third aspect of the present invention has at least the following beneficial effects:
[0024] The present invention uses compound I as a solvent in the raw material for preparing a solid electrolyte, which has good compatibility with a specific polymer and is combined with an electrolyte salt to form a uniform and stable solid electrolyte structure, thereby improving the comprehensive performance of the solid electrolyte, including ionic conductivity, electrochemical stability, and electrode interface compatibility.
[0025] In some specific embodiments of the present invention, the electrolyte salt includes at least one of a lithium salt, a sodium salt, a potassium salt, a magnesium salt, a zinc salt or an aluminum salt.
[0026] In some specific embodiments of the present invention, the anion of the electrolyte salt includes at least one of hexafluorophosphate ion, bistrifluoromethanesulfonyl imide ion, bisfluorosulfonyl imide ion, difluorooxalatoborate ion, trifluoromethanesulfonate ion, nitrate ion, perchlorate ion or tetrafluoroborate ion.
[0027] In some specific embodiments of the present invention, the mass ratio of the polymer to the electrolyte salt is 1:(1-20).
[0028] In some specific embodiments of the present invention, the mass ratio of the polymer to the solvent is 1:(0.5-5).
[0029] In some specific embodiments of the present invention, the preparation raw materials further include metal salts.
[0030] In some specific embodiments of the present invention, the mass percentage of the metal salt in the preparation raw material is 0.01-10%.
[0031] In some specific embodiments of the present invention, the metal salt includes at least one of titanium acetylacetonate, vanadium acetylacetonate, titanium tetrachloride or vanadium chloride.
[0032] In some specific embodiments of the present invention, the thickness of the solid electrolyte is 5 to 50 μm.
[0033] In some specific embodiments of the present invention, the ionic conductivity of the solid electrolyte at 30°C is ≥ 2×10 -4 Scm -1 .
[0034] In some specific embodiments of the present invention, the 75°C ionic conductivity of the solid electrolyte is ≥8×10 -4 Scm -1 .
[0035] In some specific embodiments of the present invention, the electrochemical stability window of the solid electrolyte is ≥4.3Vvs.Li / Li + .
[0036] The fourth aspect of the present invention provides a method for preparing the solid electrolyte described in the third aspect of the present invention, comprising the following steps: mixing the various preparation raw materials, forming a film, and vacuum drying to obtain the solid electrolyte.
[0037] The method for preparing the solid electrolyte according to the fourth aspect of the present invention has at least the following beneficial effects:
[0038] The vacuum drying method can ensure a uniform solid electrolyte film and reduce solvent residues. Even under vacuum drying conditions, the solvent will inevitably remain in the solid electrolyte, thereby forming a local high-concentration solvent structure. The preparation method provided by the present invention is conducive to forming a stable local high-concentration solvent structure, thereby obtaining a solid electrolyte with excellent comprehensive performance, and the preparation method is simple in process and easy to implement.
[0039] The fifth aspect of the present invention provides a solid-state battery, comprising a positive electrode material, a negative electrode material and the solid electrolyte described in the third aspect of the present invention.
[0040] The solid-state battery according to the fifth aspect of the present invention has at least the following beneficial effects:
[0041] The solid electrolyte of the third aspect of the present invention is used as an electrolyte layer and combined with positive electrode materials and negative electrode materials to obtain a solid-state battery with excellent electrochemical properties, high capacity, high rate performance, long cycle life and good safety performance.
[0042] In some specific embodiments of the present invention, the positive electrode material includes at least one of lithium iron phosphate, lithium cobalt oxide, high nickel ternary material, sulfur, sodium iron phosphate, sodium cobalt oxide, potassium iron phosphate or potassium cobalt oxide.
[0043] In some specific embodiments of the present invention, the negative electrode material includes at least one of lithium, sodium, potassium, magnesium, zinc or aluminum. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a physical photo of the solid electrolyte of Example 1.
[0045] Figure 2This is a SEM image of the solid electrolyte of Example 1.
[0046] Figure 3 The lithium ion conductivity of the solid electrolytes of Example 1 and Comparative Example 1 at different temperatures.
[0047] Figure 4 2 are LSV curves of the solid electrolytes of Example 1 and Comparative Example 1.
[0048] Figure 5 The SEM image and Ti element distribution diagram of the solid electrolyte of Example 9.
[0049] Figure 6 1. The SEM image and V element distribution diagram of the solid electrolyte of Example 10.
[0050] Figure 7 The discharge specific capacities of the batteries of Application Example 1 and Comparative Example 1 at different current densities.
[0051] Figure 8 The discharge specific capacity and coulombic efficiency of the battery of Application Example 1 at 0.2C.
[0052] Fig. 9 The discharge specific capacity and coulombic efficiency of the battery of Application Example 1 at 2C.
[0053] Fig.10 The time-voltage curves of the solid-state lithium-lithium symmetric battery of Application Example 2 and Comparative Example 2 are shown.
[0054] Fig.11 The charge and discharge specific capacity and coulombic efficiency of the battery of Application Example 3 at different current densities.
[0055] Fig.12 The voltage-specific capacity curve of the battery of Application Example 3 at different current densities. DETAILED DESCRIPTION
[0056] The content of the present invention is further described in detail by examples below. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0057] The first aspect of the embodiment of the present invention provides the use of compound I in preparing a solid electrolyte. The structural formula of compound I is shown below:
[0058]
[0059] Wherein, X1, X2, and X3 are each independently selected from hydrogen, fluorine, chlorine, bromine, iodine, hydroxyl, amino or thiol, and X1, X2, and X3 are not hydrogen at the same time, and at most only one of X1, X2, and X3 is a hydroxyl, amino or thiol group; R1 and R2 are each independently selected from substituted or unsubstituted C1~C10 straight or branched alkyl, substituted or unsubstituted C3~C10 cycloalkyl, substituted or unsubstituted C1~C10 siloxane; wherein the substituted substituent includes at least one of fluorine, chlorine, bromine or iodine; the number of substitutions ranges from single substitution to full substitution.
[0060] The present invention, through the design of the molecular structure, keeps compound I in low polarity while introducing a functional group alkoxy group that can weakly coordinate with electrolyte ions (such as lithium ions, etc.), thereby achieving multiple optimizations of compound performance. Compound I has low polarity, can significantly reduce its corrosiveness to electrode materials, and can be beneficial to improve its compatibility with electrode materials, as well as compatibility with other preparation raw materials such as polymers, to form a uniform and stable solid electrolyte structure; and compound I has high chemical stability, which is beneficial to achieving a wide electrochemical window; compound I is also beneficial to promote the dissociation of electrolyte salts such as lithium salts, thereby improving ionic conductivity; more importantly, compound I can form a stable local high-concentration solvent structure in the solid electrolyte, which is beneficial to the rapid transmission of electrolyte ions, thereby improving the room temperature ionic conductivity of the solid electrolyte. It can be seen that the present invention can greatly improve the comprehensive performance of the solid electrolyte, including ionic conductivity, electrochemical stability and electrode interface compatibility, etc., by introducing compound I, and is also beneficial to simplify the preparation process of the solid electrolyte, which provides important technical support for the development of a new generation of high-performance solid electrolytes and solid-state batteries, and is expected to promote the further development of electrochemical energy storage technology.
[0061] In some embodiments of the present invention, X1, X2, and X3 are each independently selected from hydrogen, fluorine, hydroxyl, amino, or thiol, and X1, X2, and X3 are not hydrogen at the same time, and at most only one of X1, X2, and X3 is a hydroxyl, amino, or thiol group; in some specific embodiments of the present invention, X1, X2, and X3 are each independently selected from fluorine, hydroxyl, amino, or thiol, and at most only one of X1, X2, and X3 is a hydroxyl, amino, or thiol group; in some examples of the present invention, X1, X2, and X3 are all selected from fluorine.
[0062] By changing X1, X2, and X3, the type and number of polar groups in compound I can be adjusted, thereby adjusting the molecular structure of compound I, and then adjusting its polarity, solubility, electrochemical stability, and the overall performance of the solid electrolyte, etc., to achieve the performance optimization of compound I in the preparation of solid electrolytes. Among them, by adjusting the number of introduced polar groups, the electrochemical stability of the compound can be adjusted. X1, X2, and X3 all introduce polar groups, which is beneficial to increase the electrochemical stability of compound I; using different polar groups, the compatibility and solubility of compound I with other preparation raw materials of the solid electrolyte can be adjusted, and the overall performance of the solid electrolyte can be improved. For example, different polar groups can be used according to different electrolyte salts to promote the dissolution and dissociation of electrolyte salts, thereby improving ionic conductivity, etc.
[0063] In some embodiments of the present invention, R1 and R2 are each independently selected from substituted or unsubstituted C1~C5 straight or branched alkyl, substituted or unsubstituted C3~C5 cycloalkyl, substituted or unsubstituted C1~C5 siloxane; in some specific embodiments of the present invention, R1 and R2 are each independently selected from substituted or unsubstituted C1~C5 straight or branched alkyl; in some examples of the present invention, R1 and R2 are each independently selected from substituted or unsubstituted C1~C3 straight or branched alkyl.
[0064] In some embodiments of the present invention, R1 and R2 are each independently selected from substituted or unsubstituted C1~C3 straight or branched alkyl groups, wherein the substituted substituents are selected from fluorine, and the number of substitutions is from single substitution to full substitution; in some specific embodiments of the present invention, R1 and R2 are each independently selected from methyl, ethyl, n-propyl, isopropyl, monofluoromethyl, difluoromethyl, trifluoromethyl, monofluoroethyl, difluoroethyl, pentafluoroethyl, trifluoro-n-propyl, heptafluoro-n-propyl or heptafluoro-isopropyl; in some examples of the present invention, R1 and R2 are each independently selected from methyl, ethyl, n-propyl or isopropyl; in some specific examples of the present invention, R1 and R2 are both selected from methyl.
[0065] Adjusting the side chain length and substituents of compound I can also achieve the effect of adjusting its molecular structure and performance. Adjusting the length of the side chain is conducive to optimizing the polarity and solubility of compound I; and adjusting the type and amount of the introduced polar substituents can adjust the compatibility and solubility of compound I with other preparation raw materials of the solid electrolyte, thereby improving the overall performance of the solid electrolyte.
[0066] In some specific examples of the present invention, compound I is selected from compound A shown below:
[0067]
[0068] It is understandable that the compounds that can achieve the above technical effects of the present invention are not limited to compound A. Compound A is only a specific example. Compound I that conforms to the description of the present invention is the protection content of the present invention.
[0069] In some embodiments of the present invention, Compound I is used as a solvent for preparing a solid electrolyte.
[0070] In some embodiments of the present invention, the solid electrolyte is used to prepare a solid-state battery, such as a solid-state lithium-ion battery, a solid-state lithium-sulfur battery, a solid-state potassium-ion battery, a solid-state sodium-ion battery, a solid-state magnesium-ion battery, a solid-state zinc-ion battery, a solid-state aluminum-ion battery, etc.
[0071] A second aspect of an embodiment of the present invention provides a solvent for preparing a solid electrolyte, including compound I in the application of the first aspect of an embodiment of the present invention.
[0072] When compound I is used as a solvent for preparing solid electrolytes, due to its low polarity, it is beneficial to improve the electrochemical stability and electrode interface compatibility of the solid electrolyte structure, and its alkoxy group can weakly coordinate with electrolyte ions (such as lithium ions, etc.), promote the dissociation of electrolyte salts, thereby improving the ionic conductivity of the solid electrolyte. Therefore, using compound I as a solvent for preparing solid electrolytes is conducive to obtaining high-performance solid electrolytes and solid-state batteries.
[0073] The third aspect of the embodiment of the present invention provides a solid electrolyte, comprising the following preparation raw materials: a polymer, an electrolyte salt, and a solvent of the second aspect of the embodiment of the present invention; the polymer comprises at least one of a fluorinated polymer, a polyolefin polymer, a polynitrile polymer, a polyether polymer, a polyester polymer, a polyacrylate polymer, a chlorine-containing polymer or a polysiloxane polymer.
[0074] In the embodiment of the present invention, compound I is used as a solvent in the raw material for preparing the solid electrolyte, which has good compatibility with a specific polymer and is combined with an electrolyte salt to form a uniform and stable solid electrolyte structure, thereby improving the comprehensive performance of the solid electrolyte, including ionic conductivity, electrochemical stability, and electrode interface compatibility.
[0075] In some embodiments of the present invention, the fluorinated polymer includes at least one of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), or polyperfluoroalkylethyl ether (PFA).
[0076] In some embodiments of the present invention, the polyolefin polymer includes polyethylene (PE), polypropylene (PP) or a combination thereof.
[0077] In some embodiments of the present invention, the polynitrile polymer includes polyacrylonitrile (PAN), polybutadienenitrile (PBN), or a combination thereof.
[0078] In some embodiments of the present invention, the polyether polymer includes at least one of polyethylene oxide (PEO), polypropylene oxide (PPO) or polytetrahydrofuran (PTHF).
[0079] In some embodiments of the present invention, the polyester polymer includes polycarbonate (PC), polyethylene carbonate (PEC) or a combination thereof.
[0080] In some embodiments of the present invention, the polyacrylate polymer includes polymethyl methacrylate (PMMA), polyacrylic acid (PAA), or a combination thereof.
[0081] In some embodiments of the present invention, the chlorine-containing polymer includes at least one of polyvinyl chloride (PVC), chlorinated polyethylene (CPE), or polyvinylidene chloride (PVDC).
[0082] In some embodiments of the present invention, the polysiloxane-based polymer includes polydimethylsiloxane (PDMS).
[0083] In some embodiments of the present invention, polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), polyperfluoroalkylethyl ether (PFA), polyethylene (PE), polypropylene (PP), polyacrylonitrile (PAN), polybutadiene nitrile (PBN), polyethylene oxide (PEO), polypropylene oxide (PPO), polytetrahydrofuran (PTHF), polycarbonate (PC), polyethylene carbonate (PEC), polymethyl methacrylate (PMMA), polyacrylic acid (PAA), polyvinyl chloride (PVC), chlorinated polyethylene (CPE), polyvinylidene chloride (PVD), polyvinyl chloride (PVF), polyvinyl chloride (PVD ...PTFE), polyvinyl chloride (PVD), polyvinyl chloride (PVD), polyvinyl chloride (PTFE), polyvinyl chloride (PVD), polyvinyl chloride (PVD), polyvinyl chloride (PTFE), polyvinyl chloride (PVD), polyvinyl chloride (PVD), polyvinyl chloride (PTFE), polyvinyl chloride (PVD), polyvinyl chloride (PVD), polyvinyl chloride (PTFE), polyvinyl chloride (PVD), polyvinyl chloride (PVD), polyvinyl chloride (PTFE), polyvinyl chloride (PVD), polyvinyl chloride (PVD), polyvinyl chloride ( DC) or polydimethylsiloxane (PDMS); in some specific embodiments of the present invention, the polymer includes at least one of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyethylene oxide (PEO) or polymethyl methacrylate (PMMA); in some examples of the present invention, the polymer includes at least one of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyacrylonitrile (PAN) or polyethylene oxide (PEO); in some specific examples of the present invention, the polymer is selected from polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0084] The solvent in the embodiment of the present invention has good compatibility with the polymer, and the combination of the two can prepare a solid electrolyte with excellent performance. By adjusting the type of polymer, the ionic conductivity and mechanical strength of the solid electrolyte can be adjusted, so that the solid electrolyte still has outstanding performance under high temperature and high voltage conditions. In particular, the solvent in the embodiment of the present invention has good compatibility with polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and is particularly suitable for preparing high-performance polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP)-based solid electrolytes.
[0085] In some embodiments of the present invention, the electrolyte salt includes at least one of a lithium salt, a sodium salt, a potassium salt, a magnesium salt, a zinc salt or an aluminum salt; in some specific embodiments of the present invention, the electrolyte salt includes at least one of a lithium salt, a sodium salt or a potassium salt; in some examples of the present invention, the electrolyte salt includes one of a lithium salt, a sodium salt or a potassium salt.
[0086] In some embodiments of the present invention, the anion of the electrolyte salt includes at least one of hexafluorophosphate ion, bistrifluoromethanesulfonyl imide ion, bisfluorosulfonyl imide ion, difluorooxalatoborate ion, trifluoromethanesulfonate ion, nitrate ion, perchlorate ion or tetrafluoroborate ion.
[0087] The solvent of the present invention has good solubility for various electrolyte salts. Therefore, the present invention can use lithium salts, sodium salts or potassium salts as electrolyte salts, thereby obtaining different types of solid electrolytes and solid-state batteries, such as solid-state lithium ion batteries, solid-state lithium sulfur batteries, solid-state sodium ion batteries or solid-state potassium ion batteries.
[0088] In some embodiments of the present invention, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium bisfluorosulfonyl imide (LiFSI), lithium difluorooxalate borate (LiDFOB), lithium trifluoromethanesulfonate (LiCF3SO3), lithium nitrate (LiNO3), lithium perchlorate (LiClO4) or lithium tetrafluoroborate (LiBF4); in some specific embodiments of the present invention, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI) or lithium difluorooxalate borate (LiDFOB).
[0089] In some embodiments of the present invention, the sodium salt includes at least one of sodium hexafluorophosphate (NaPF6), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium bis(fluorosulfonyl)imide (NaFSI), sodium difluorooxalatoborate (NaDFOB), sodium trifluoromethanesulfonate (NaCF3SO3), sodium nitrate (NaNO3), sodium perchlorate (NaClO4) or sodium tetrafluoroborate (NaBF4); in some specific embodiments of the present invention, the sodium salt includes at least one of sodium hexafluorophosphate (NaPF6), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium perchlorate (NaClO4) or sodium tetrafluoroborate (NaBF4).
[0090] In some embodiments of the present invention, the potassium salt includes at least one of potassium hexafluorophosphate (KPF6), potassium bistrifluoromethanesulfonyl imide (KTFSI), potassium bisfluorosulfonyl imide (KFSI), potassium difluorooxalate borate (KDFOB), potassium trifluoromethanesulfonate (KCF3SO3), potassium nitrate (KNO3), potassium perchlorate (KClO4) or potassium tetrafluoroborate (KBF4); in some specific embodiments of the present invention, the potassium salt includes at least one of potassium hexafluorophosphate (KPF6), potassium bistrifluoromethanesulfonyl imide (KTFSI) or potassium difluorooxalate borate (KDFOB).
[0091] In some embodiments of the present invention, the magnesium salt includes at least one of magnesium hexafluorophosphate (Mg(PF6)2), magnesium bis(trifluoromethanesulfonyl imide) (Mg(TFSI)2), magnesium bis(fluorosulfonyl imide) (Mg(FSI)2), magnesium difluorooxalate borate (Mg(DFOB)2), magnesium trifluoromethanesulfonate (Mg(CF3SO3)2), magnesium nitrate (Mg(NO3)2), magnesium perchlorate (Mg(ClO4)2) or magnesium tetrafluoroborate (Mg(BF4)2); in some specific embodiments of the present invention, the magnesium salt includes magnesium perchlorate (Mg(ClO4)2), magnesium bis(trifluoromethanesulfonyl imide) (Mg(TFSI)2) or a combination thereof.
[0092] In some embodiments of the present invention, the zinc salt includes at least one of zinc hexafluorophosphate (Zn(PF6)2), zinc bistrifluoromethanesulfonyl imide (Zn(TFSI)2), zinc bisfluorosulfonyl imide (Zn(FSI)2), zinc difluorooxalate borate (Zn(DFOB)2), zinc trifluoromethanesulfonate (Zn(CF3SO3)2), zinc nitrate (Zn(NO3)2), zinc perchlorate (Zn(ClO4)2) or zinc tetrafluoroborate (Zn(BF4)2); in some specific embodiments of the present invention, the zinc salt includes zinc trifluoromethanesulfonate (Zn(CF3SO3)2), or zinc tetrafluoroborate (Zn(BF4)2) or a combination thereof.
[0093] In some embodiments of the present invention, the aluminum salt includes at least one of lithium tetrachloroaluminate (LiAlCl4), aluminum hexafluorophosphate (Al(PF6)3), bistrifluoromethanesulfonyl imide aluminum (Al(TFSI)3), bisfluorosulfonyl imide aluminum (Al(FSI)3), difluorooxalatoaluminum borate (Al(DFOB)3), aluminum trifluoromethanesulfonate (Al(CF3SO3)3), aluminum nitrate (Al(NO3)3), aluminum perchlorate (Al(ClO4)3), and aluminum tetrafluoroborate (Al(BF4)3); in some specific embodiments of the present invention, the aluminum salt is selected from lithium tetrachloroaluminate (LiAlCl4).
[0094] In some embodiments of the present invention, the mass ratio of polymer to solvent is 1:(1-20); in some specific embodiments of the present invention, the mass ratio of polymer to solvent is 1:(3-15); in some examples of the present invention, the mass ratio of polymer to solvent is 1:(5-10). Non-limiting examples are 1:6, 1:7, 1:8 or 1:9.
[0095] In some embodiments of the present invention, the mass ratio of polymer to electrolyte salt is 1:(0.5-5); in some specific embodiments of the present invention, the mass ratio of polymer to electrolyte salt is 1:(0.8-3); in some examples of the present invention, the mass ratio of polymer to electrolyte salt is 1:(1-2). Non-limiting specific examples are 1:1.2, 1:1.4, 1:1.6 or 1:1.8.
[0096] In some embodiments of the present invention, the preparation raw materials further include metal salts.
[0097] The embodiment of the present invention further adds metal salts to the raw materials for preparing the solid electrolyte, which is beneficial to further stabilize the local high-concentration solvent structure and significantly improve the ionic conductivity and electrochemical stability of the solid electrolyte. In other words, the addition of metal salts is beneficial to improving the performance of the solid electrolyte, such as stability and conductivity at different temperatures and current densities.
[0098] In some embodiments of the present invention, the mass percentage of the metal salt in the raw material is 0.01-10%; in some specific embodiments of the present invention, the mass percentage of the metal salt in the raw material is 0.05-8%; in some examples of the present invention, the mass percentage of the metal salt in the raw material is 0.1-5%. Non-limiting specific examples are 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%.
[0099] In some embodiments of the present invention, the metal salt includes at least one of titanium acetylacetonate, vanadium acetylacetonate, titanium tetrachloride or vanadium chloride; in some specific embodiments of the present invention, the metal salt includes titanium acetylacetonate, vanadium acetylacetonate or a combination thereof.
[0100] In some embodiments of the present invention, the thickness of the solid electrolyte is 5 to 50 μm; in some specific embodiments of the present invention, the thickness of the solid electrolyte is 10 to 40 μm; in some examples of the present invention, the thickness of the solid electrolyte is 15 to 30 μm. Non-limiting specific examples are 18 μm, 20 μm, 22 μm, 25 μm or 28 μm.
[0101] In some embodiments of the present invention, the ionic conductivity of the solid electrolyte at 30°C is ≥ 2×10 -4 S cm -1 In some specific embodiments of the present invention, the ionic conductivity of the solid electrolyte at 30°C is (2-10)×10 -4 S cm -1 In some examples of the present invention, the ionic conductivity of the solid electrolyte at 30°C is (3-6)×10 -4 S cm -1 A non-limiting example is 3.5×10 -4 S cm -1 , 4×10 -4 S cm -1 , 4.5×10 -4 S cm -1 , 5×10 -4 S cm -1 or 5.5×10 -4 S cm -1 .
[0102] The solid electrolyte in the embodiment of the present invention has good room temperature (30° C.) ionic conductivity. The test frequency range of the 30° C. ionic conductivity is 0.01 Hz to 1 MHz.
[0103] In some embodiments of the present invention, the ionic conductivity of the solid electrolyte at 75°C is ≥ 8×10 -4 S cm -1 In some specific embodiments of the present invention, the ionic conductivity of the solid electrolyte at 75°C is (8-20)×10 -4 S cm -1 In some examples of the present invention, the ionic conductivity of the solid electrolyte at 75°C is (10-15)×10 -4 S cm -1 A non-limiting example is 11×10 -4 S cm -1 , 12×10 -4 S cm -1 , 13×10 -4 S cm -1 or 14×10 -4S cm -1 .
[0104] The solid electrolyte in the embodiment of the present invention also has good high temperature (75° C.) ion conductivity. The test frequency range of the above 75° C. ion conductivity is 0.01 Hz to 1 MHz.
[0105] In some embodiments of the present invention, the electrochemical stability window of the solid electrolyte is ≥ 4.3V vs. Li / Li + In some specific embodiments of the present invention, the electrochemical stability window of the solid electrolyte is 4.3-5V vs. Li / Li + In some examples of the present invention, the electrochemical stability window of the solid electrolyte is 4.5-5V vs. Li / Li + A non-limiting example is 4.6V vs. Li / Li + , 4.7V vs.Li / Li + , 4.8V vs.Li / Li + or 4.9V vs.Li / Li + .
[0106] The solid electrolyte in the embodiment of the present invention has a wide electrochemical stability window. The above electrochemical stability window is measured at room temperature (30° C.).
[0107] A fourth aspect of an embodiment of the present invention provides a method for preparing the solid electrolyte of the third aspect of an embodiment of the present invention, comprising the following steps: mixing various preparation raw materials, forming a film, and vacuum drying to obtain a solid electrolyte.
[0108] The vacuum drying method can ensure a uniform solid electrolyte film and reduce solvent residues. Even under vacuum drying conditions, the solvent will inevitably remain in the solid electrolyte, thereby forming a local high-concentration solvent structure. The preparation method provided by the present invention is conducive to forming a stable local high-concentration solvent structure, thereby obtaining a solid electrolyte with excellent comprehensive performance, and the preparation method is simple in process and easy to implement.
[0109] In some embodiments of the present invention, the temperature for mixing the raw materials is 60-90° C.; in some specific embodiments of the present invention, the temperature for mixing the raw materials is 70-85° C.; in some examples of the present invention, the temperature for mixing the raw materials is 75-80° C. Non-limiting specific examples include 76° C., 77° C., 78° C., or 79° C.
[0110] In some embodiments of the present invention, the time for mixing the raw materials is 0.1 to 10 hours; in some specific embodiments of the present invention, the time for mixing the raw materials is 0.3 to 7 hours; in some examples of the present invention, the time for mixing the raw materials is 0.5 to 5 hours. Non-limiting specific examples include 1 hour, 2 hours, 3 hours or 4 hours.
[0111] In some embodiments of the present invention, the raw materials are mixed in a specific manner: firstly, the polymer is mixed with the solvent, and then the electrolyte salt is added for mixing. In other embodiments of the present invention, the raw materials also include metal salts, and the raw materials are mixed in a specific manner: firstly, the metal salt is mixed with the solvent, and then the polymer is added for mixing, and then the electrolyte salt is added for mixing.
[0112] In some embodiments of the present invention, the vacuum drying temperature is 50-70°C; in some specific embodiments of the present invention, the vacuum drying temperature is 52-68°C; in some examples of the present invention, the vacuum drying temperature is 55-65°C. Non-limiting specific examples are 57°C, 59°C, 60°C, 61°C or 63°C.
[0113] In some embodiments of the present invention, the vacuum drying time is 0.5 to 5 hours; in some specific embodiments of the present invention, the vacuum drying time is 1 to 4 hours; in some examples of the present invention, the vacuum drying time is 1.5 to 3 hours. Non-limiting specific examples include 1.8 hours, 2 hours, 2.2 hours, 2.5 hours or 2.8 hours.
[0114] In some embodiments of the present invention, the film forming method is casting film forming; in some specific embodiments of the present invention, the casting film forming is normal pressure casting film forming. The casting step is conducive to forming a uniform film structure.
[0115] A fourth aspect of the embodiments of the present invention provides a solid-state battery, comprising a positive electrode material, a negative electrode material and the solid-state electrolyte of the third aspect of the embodiments of the present invention.
[0116] The solid electrolyte of the third aspect of the embodiment of the present invention is used as an electrolyte layer and combined with positive electrode materials and negative electrode materials to obtain a solid-state battery with excellent electrochemical properties, high capacity, high rate performance, long cycle life and good safety performance.
[0117] In some embodiments of the present invention, the positive electrode material includes at least one of lithium iron phosphate (LFP), lithium cobalt oxide (LCO), high nickel ternary material (NCM), sulfur (S), sodium iron phosphate (NVP), sodium cobalt oxide (NaCoO2), potassium iron phosphate (KFePO4) or potassium cobalt oxide (KCoO2).
[0118] In some embodiments of the present invention, the structural formula of the high nickel ternary material is LiNi (1-x-y) Co x Mn y O2, wherein x is 0.01 to 0.1, and y is 0.01 to 0.1; in some specific embodiments of the present invention, the structural formula of the high nickel ternary material is LiNi (1-x-y) Co x Mn y O2, wherein x is 0.03 to 0.07, and y is 0.03 to 0.07; in some examples of the present invention, the structural formula of the high nickel ternary material is LiNi 0.9 Co 0.05 Mn 0.05 O2(NCM91).
[0119] In some embodiments of the present invention, the negative electrode material includes at least one of lithium, sodium, potassium, magnesium, zinc or aluminum.
[0120] The solid electrolyte of the present invention can be used in combination with various positive electrode materials to obtain various types of solid battery materials.
[0121] In some embodiments of the present invention, the solid-state battery includes at least one of a solid-state lithium-ion battery, a solid-state lithium-sulfur battery, a solid-state potassium-ion battery, a solid-state sodium-ion battery, a solid-state magnesium-ion battery, a solid-state zinc-ion battery or a solid-state aluminum-ion battery; in some specific embodiments of the present invention, the solid-state battery includes at least one of a solid-state lithium-ion battery, a solid-state lithium-sulfur battery, a solid-state potassium-ion battery or a solid-state sodium-ion battery.
[0122] In some embodiments of the present invention, in a solid-state lithium-ion battery, when lithium iron phosphate is used as the positive electrode material, at 30°C and a current density of 0.1 to 2C, the discharge capacity of the lithium metal battery is ≥140 mAh g -1 In some specific embodiments of the present invention, in a solid-state lithium-ion battery, when lithium iron phosphate is used as the positive electrode material, at 30°C and a current density of 0.1 to 2C, the discharge specific capacity of the lithium metal battery is 140 to 200 mAh g -1 .
[0123] In some non-limiting specific examples of the present invention, when lithium iron phosphate is used as the positive electrode material, at 30°C, when the current density is 0.1C, 0.2C, 1C, and 2C, the discharge specific capacity is not less than 172 mAh·g -1 、170mAh·g -1 、165mAh·g -1 , 150mAh·g -1 .
[0124] In some embodiments of the present invention, in a solid-state lithium-ion battery, when lithium iron phosphate is used as the positive electrode material, after 500 cycles at a current density of 2C, the capacity retention rate of the lithium metal battery is ≥85%; in some specific embodiments of the present invention, in a solid-state lithium-ion battery, when lithium iron phosphate is used as the positive electrode material, after 500 cycles at a current density of 2C, the capacity retention rate of the lithium metal battery is 85-95%. Non-limiting specific examples are 88%, 90% or 92%.
[0125] In some embodiments of the present invention, in a solid-state lithium-ion battery, when a high-nickel ternary material is used as a positive electrode material, the discharge capacity of the lithium metal battery is ≥150 mAh g at a current density of 0.1 to 2 C. -1 In some specific embodiments of the present invention, in a solid-state lithium-ion battery, when a high-nickel ternary material is used as a positive electrode material, the discharge capacity of the lithium metal battery is 150 to 220 mAh g at a current density of 0.1 to 2C. -1 .
[0126] In some non-limiting specific examples of the present invention, when using high nickel ternary material LiNi 0.9 Co 0.05 Mn 0.05 When O2 is used as the positive electrode material, at 30°C, the discharge capacity is not less than 200 mAh g at current densities of 0.1C, 0.2C, 0.5C, 1C, and 2C. -1 、195mAh·g -1 、190mAh·g -1 、180mAh·g -1 、160mAh·g -1 .
[0127] The present invention is further described below in conjunction with more specific embodiments and comparative examples.
[0128] Example 1
[0129] In this example, N-methoxy-N-methyl-2,2,2-trifluoroacetamide (TFOMA) is used as a solvent to prepare a solid electrolyte. N-methoxy-N-methyl-2,2,2-trifluoroacetamide (TFOMA) is compound A, and its structural formula is as follows:
[0130]
[0131] In this example, the raw materials for preparing the solid electrolyte include:
[0132] (1) Solvent: the above-mentioned compound A (TFOMA);
[0133] (2) Polymer: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP);
[0134] (3) Lithium salt: lithium trifluoromethanesulfonyl imide (LiTFSI);
[0135] The mass ratio of PVDF-HFP to TFOMA is 1:8; the mass ratio of PVDF-HFP to LiTFSI is 1:1.
[0136] The preparation method of the solid electrolyte comprises the following steps:
[0137] (1) Dissolution: Add PVDF-HFP to TFOMA in proportion and stir until completely dissolved to form a uniform polymer solution; then, add LiTFSI to the polymer solution and continue stirring until the lithium salt is completely dissolved;
[0138] (2) Mixing: Stir at 75°C for 30 minutes to ensure sufficient mixing and dissolution;
[0139] (3) Casting: solution casting is performed under normal pressure to form a uniform film;
[0140] (4) Vacuum drying: vacuum drying was performed at 60°C for 2 h to obtain the final solid electrolyte membrane, which was denoted as PVDF-HFP@TFOMA.
[0141] Comparative Example 1
[0142] In this example, the traditional solvent N,N-dimethyltrifluoroacetamide (TFDMA) is used as a solvent to prepare a solid electrolyte. The structural formula of N,N-dimethyltrifluoroacetamide (TFDMA) is as follows:
[0143]
[0144] The solid electrolyte in this example is different from the solid electrolyte in Example 1 only in the solvent, and the other preparation materials and preparation methods are the same as those in Example 1. The solid electrolyte membrane in this example is denoted as PVDF-HFP@TFDMA.
[0145] Performance testing and analysis
[0146] (1) Morphological characterization: Scanning electron microscopy (SEM) was used to characterize and analyze the two solid electrolytes of Example 1 and Comparative Example 1. Since the PVDF-HFP-based solid electrolyte membrane has poor conductivity, the sample surface needs to be gold-sprayed before SEM testing to improve imaging quality.
[0147] (2) Ion conductivity test: The lithium ion conductivity of the two solid electrolytes of Example 1 and Comparative Example 1 at different temperatures (20-75° C.) was tested by electrochemical impedance spectroscopy (EIS), and the test frequency range was 0.01 Hz to 1 MHz.
[0148] (3) Electrochemical stability window test: The voltage stability windows of the two solid electrolytes of Example 1 and Comparative Example 1 were tested by linear sweep voltammetry (LSV).
[0149] Figure 1 This is a real photo of the solid electrolyte of Example 1. It can be seen that the electrolyte membrane is transparent and has an extremely thin thickness. Figure 2 : SEM images of the solid electrolyte of Example 1, wherein (a) is the SEM image of the electrolyte membrane plane, and (b) is the SEM image of the electrolyte membrane cross-section. It can be seen that the PVDF-HFP@TFOMA electrolyte membrane of Example 1 is uniform in plane and cross-section, has excellent surface smoothness and structural integrity, and the thickness of the electrolyte membrane is about 23 μm.
[0150] Figure 3 The lithium ion conductivity of the solid electrolytes of Example 1 and Comparative Example 1 at different temperatures. It can be seen that the ion conductivity of the solid electrolyte PVDF-HFP@TFOMA of Example 1 at room temperature (30°C) is as high as 4×10 -4 S cm -1 The above is significantly higher than the solid electrolyte PVDF-HFP@TFDMA in comparative example 1; the ionic conductivity of the solid electrolyte PVDF-HFP@TFOMA in example 1 at 75°C is as high as 1.2×10 -3 S cm -1 , which is also significantly higher than the solid electrolyte PVDF-HFP@TFDMA in Comparative Example 1.
[0151] Figure 4 : The LSV curves of the solid electrolytes of Example 1 and Comparative Example 1. It can be seen that the electrochemical stability window of PVDF-HFP@TFOMA of Example 1 can reach 4.5V vs.Li / Li + , while the electrochemical stability window of PVDF-HFP@TFDMA in comparative example 1 is only 4.25V vs.Li / Li + Therefore, the use of TFOMA as a solvent in Example 1 is beneficial to broadening the electrochemical stability window of the solid electrolyte.
[0152] Example 2
[0153] This example provides a solid electrolyte, which is different from the solid electrolyte in Example 1 in that the mass ratio of PVDF-HFP to TFOMA in the preparation raw materials of this example is 1:5; step (2) in the preparation method is stirring at 80°C for 2 hours to ensure sufficient mixing and dissolution; other preparation raw materials and preparation methods are the same as in Example 1.
[0154] Example 3
[0155] This example provides a solid electrolyte, which is different from the solid electrolyte in Example 1 in that the mass ratio of PVDF-HFP to TFOMA in the preparation raw materials of this example is 1:6; step (2) in the preparation method is stirring at 80°C for 1.5 hours to ensure sufficient mixing and dissolution; other preparation raw materials and preparation methods are the same as in Example 1.
[0156] Example 4
[0157] This example provides a solid electrolyte, which is different from the solid electrolyte in Example 1 in that the mass ratio of PVDF-HFP to TFOMA in the preparation raw materials of this example is 1:7; step (2) in the preparation method is stirring at 80°C for 1 hour to ensure sufficient mixing and dissolution; other preparation raw materials and preparation methods are the same as in Example 1.
[0158] Example 5
[0159] This example provides a solid electrolyte, which is different from the solid electrolyte in Example 1 in that the mass ratio of PVDF-HFP to TFOMA in the preparation raw materials of this example is 1:9; other preparation raw materials and preparation methods are the same as those in Example 1.
[0160] Example 6
[0161] This example provides a solid electrolyte, which is different from the solid electrolyte in Example 1 in that the mass ratio of PVDF-HFP to TFOMA in the preparation raw materials of this example is 1:10; other preparation raw materials and preparation methods are the same as those in Example 1.
[0162] In order to study the effect of different raw material ratios on the dissolution rate and coating thickness of the material, Examples 2 to 6 changed the ratio of polymer to solvent based on Example 1. It can be seen that under the conditions of PVDF-HFP to TFOMA mass ratios of 1:5, 1:6, and 1:7, PVDF-HFP needs to be stirred at 80°C for 2 hours, 1.5 hours, and 1 hour respectively to be completely dissolved; and under the conditions of mass ratios of 1:8, 1:9, and 1:10, PVDF-HFP only needs to be stirred at 75°C for 30 minutes to be completely dissolved. In addition, as the proportion of TFOMA solvent increases, the thickness of the solid electrolyte membrane after coating gradually decreases, and the maximum film thickness of about 20μm can be achieved, which is suitable for application scenarios that require fine control of coating thickness.
[0163] Example 7
[0164] This example provides a solid electrolyte. The difference from the solid electrolyte in Example 1 is that the lithium salt is replaced by lithium hexafluorophosphate (LiPF6) in this example, and the other preparation raw materials and preparation methods are the same as those in Example 1.
[0165] Example 8
[0166] This example provides a solid electrolyte. The difference from the solid electrolyte in Example 1 is that the lithium salt in this example is replaced by lithium difluorooxalatoborate (LiDFOB). Other preparation raw materials and preparation methods are the same as those in Example 1.
[0167] In order to study the effect of different lithium salts on the performance of PVDF-HFP@TFOMA solid electrolyte membrane, Examples 7 to 8 changed the type of lithium salt on the basis of Example 1, and the ionic conductivity and electrochemical stability window of the obtained solid electrolyte membrane were tested using the test method of Example 1.
[0168] The results show that the solid electrolytes of Examples 7 to 8 all have good electrochemical properties, including high ionic conductivity and a wide electrochemical stability window.
[0169] Example 9
[0170] This example provides a solid electrolyte. The difference from the solid electrolyte in Example 1 is that the raw materials for preparing the solid electrolyte in this example also include a metal salt titanium acetylacetonate (C 10 H 14 O5Ti), and other preparation raw materials are the same as those in Example 1.
[0171] The preparation method of the solid electrolyte of this example comprises the following steps:
[0172] (1) Dissolution: Add a small amount of titanium acetylacetonate to the TFOMA solvent, then add PVDF-HFP in proportion, stir until completely dissolved, and form a uniform polymer solution; then, add LiTFSI to the polymer solution, and continue stirring until the lithium salt is completely dissolved; (2) to (4) steps are the same as (2) to (4) steps of Example 1. The solid electrolyte membrane of this example is recorded as PVDF-HFP@Ti@TFOMA.
[0173] Example 10
[0174] This example provides a solid electrolyte. The difference from the solid electrolyte of Example 9 is that the metal salt is replaced by vanadium acetylacetonate (C 10 H 14 O5V), and other raw materials and preparation methods are the same as those in Example 9. The solid electrolyte membrane of this example is recorded as PVDF-HFP@V@TFOMA.
[0175] In order to study the effect of metal salts on the performance of PVDF-HFP@TFOMA solid electrolyte membrane, Examples 9 to 10 added titanium acetylacetonate and vanadium acetylacetonate as metal salts, respectively, on the basis of Example 1, and tested the surface morphology and metal element distribution of the obtained solid electrolyte membrane, and used the test method of Example 1 to test the ionic conductivity and electrochemical stability window.
[0176] Figure 5 The SEM image and Ti element distribution map of the solid electrolyte of Example 9, wherein (a) is the SEM image of the electrolyte membrane plane, and (b) is the mapping image of the Ti element. Figure 6 The SEM images and V element distribution images of the solid electrolyte of Example 10, wherein (a) is the SEM image of the cross section of the electrolyte membrane, and (b) is the mapping image of the V element. Figures 5-6 It can be seen that the addition of metal salts will not affect the surface morphology of the electrolyte membrane. After adding metal salts, an electrolyte membrane with excellent surface smoothness and structural integrity can also be obtained, and the metal elements Ti and V can be evenly distributed in the electrolyte membrane.
[0177] In addition, by introducing titanium acetylacetonate in Example 9, the ionic conductivity of the solid electrolyte PVDF-HFP@Ti@TFOMA was further improved to 1.5×10 -4 S cm -1 , and the electrochemical stability window is extended to 4.7V vs.Li / Li + In Example 10, by introducing vanadium acetylacetonate, the solid electrolyte PVDF-HFP@V@TFOMA obtained has better stability at high temperature.
[0178] Embodiment 11
[0179] This example provides a solid electrolyte. The difference from the solid electrolyte in Example 1 is that the lithium salt in this example is replaced by sodium salt sodium trifluoromethanesulfonimide (NaTFSI), and the other preparation raw materials and preparation methods are the same as those in Example 1.
[0180] Example 12
[0181] This example provides a solid electrolyte. The difference from the solid electrolyte in Example 1 is that the lithium salt in this example is replaced by potassium salt potassium trifluoromethanesulfonimide (KTFSI), and the other preparation raw materials and preparation methods are the same as those in Example 1.
[0182] In Examples 11 to 12, the lithium salt is replaced by sodium salt and potassium salt, and the obtained solid electrolytes have good electrochemical properties, including high ionic conductivity and a wide electrochemical stability window, which can be used to prepare solid-state sodium ion batteries and solid-state potassium ion batteries with high electrochemical performance.
[0183] Application Example 1
[0184] A solid-state lithium-ion battery comprises a positive electrode material of lithium iron phosphate (LiFePO4), a negative electrode material of a metal lithium sheet, and a solid electrolyte membrane PVDF-HFP@TFOMA of Example 1. The specific preparation process of the battery is as follows:
[0185] (1) Preparation of positive electrode sheet: LiFePO4 positive electrode material, conductive carbon black and PVDF binder were mixed in a mass ratio of 8:1:1, and N-methyl-2-pyrrolidone (NMP) solvent was added and stirred to form a slurry. The slurry was evenly coated on aluminum foil, dried at 80°C for 12 hours, and then pressed into a positive electrode sheet.
[0186] (2) Battery assembly: The prepared positive electrode sheet, PVDF-HFP@TFOMA solid electrolyte membrane and metal lithium sheet are stacked in sequence, and assembled into a CR2032 button battery after adding a separator.
[0187] (3) Packaging: The battery is packaged at a pressure of 100 MPa in an inert gas atmosphere to prevent oxidation and moisture.
[0188] Application Comparative Example 1
[0189] A solid-state lithium-ion battery, which is different from Application Example 1 in that the solid electrolyte membrane of this example is the PVDF-HFP@TFDMA of Comparative Example 1, and other preparation materials and preparation methods are the same as those of Application Example 1.
[0190] Performance Testing
[0191] (1) Rate performance test: At 30°C, the discharge specific capacity of the battery was tested at different current densities (0.1C, 0.2C, 0.5C, 1C, 2C) to evaluate its rate performance.
[0192] (2) Cycle performance test: At 30°C, the discharge specific capacity and coulombic efficiency of the battery were tested at current densities of 0.2C and 2C, and a long cycle performance test was performed to evaluate the cycle stability of the battery.
[0193] Figure 7 The discharge specific capacities of the batteries of Application Example 1 and Comparative Example 1 at different current densities show that the solid electrolyte PVDF-HFP@TFOMA of Example 1 exhibits excellent rate performance when matched with the LiFePO4 positive electrode material, especially at high current density, the discharge specific capacity is maintained at a high level. In contrast, the performance of the solid electrolyte PVDF-HFP@TFDMA of Comparative Example 1 is significantly inferior to that of Example 1.
[0194] Figure 8 The discharge specific capacity and coulombic efficiency of the battery in Application Example 1 at 0.2C are: Fig. 9 The discharge specific capacity and coulombic efficiency of the battery of Application Example 1 at 2C show that when the solid electrolyte PVDF-HFP@TFOMA of Example 1 is matched with the LiFePO4 positive electrode material, the obtained battery has a high retention rate of discharge specific capacity and coulombic efficiency in the long cycle performance test, and the battery has good cycle stability. Specifically, when the solid electrolyte PVDF-HFP@TFOMA of Example 1 is matched with the LiFePO4 positive electrode material, the capacity retention rate is 97% after 275 cycles at 0.2C; after 500 cycles at 2C, the capacity retention rate is 88%. In contrast, the solid electrolyte PVDF-HFP@TFDMA of Comparative Example 1 has poor cycle stability and low capacity retention rate.
[0195] Application Example 2
[0196] A solid-state lithium-lithium symmetrical battery, which differs from Application Example 1 in that the positive electrode material and the negative electrode material in this example are both metal lithium sheets, and other preparation raw materials and preparation methods are the same as those in Application Example 1.
[0197] Application Comparative Example 2
[0198] A solid-state lithium-lithium symmetrical battery, which differs from application comparative example 1 in that the positive electrode material and the negative electrode material in this example are both metal lithium sheets, and other preparation raw materials and preparation methods are the same as those in application comparative example 1.
[0199] The time-voltage curves of the batteries of Application Example 2 and Comparative Example 2 were tested. Fig.10The time-voltage curves of the solid-state lithium-lithium symmetric battery of Application Example 2 and Application Comparative Example 2. These curves reflect several key performance indicators of the electrolyte: (1) Polarization characteristics: The voltage amplitude of the curve reflects the polarization degree of the battery at different current densities. Lower polarization indicates that the electrolyte has excellent ionic conductivity and interface transport properties. (2) Interface stability: The smoothness of the curve indicates the stability of the lithium metal-electrolyte interface, which is crucial to long-term cycle performance. (3) Current density adaptability: The ability to maintain low polarization at higher current density reflects the fast charge and discharge performance of the electrolyte. (4) Long-term cycle stability: The trend of the curve over time reflects the long-term cycle stability of the battery. (5) Coulomb efficiency: The symmetry of the charge and discharge curve indicates the reversibility of the lithium deposition / stripping process and reflects the coulomb efficiency of the battery. (6) By comparing the curves of Application Example 2 and Application Comparative Example 2, it can be clearly seen that the advantages of the newly developed electrolyte in the present invention in these key performance indicators, especially lower polarization and better stability at high current density. These characteristics are of great significance for the development of high-performance solid-state lithium batteries.
[0200] Application Example 3
[0201] A solid-state lithium-ion battery, which differs from Application Example 1 in that the positive electrode material in this example is replaced with a high-nickel ternary material (LiNi 0.9 Co 0.05 Mn 0.05 O2, NCM91), other raw materials and preparation methods are the same as those in Application Example 1.
[0202] Application Example 4
[0203] A solid-state lithium-sulfur battery, which differs from Application Example 1 in that the positive electrode material in this example is replaced with sulfur (S), and other preparation raw materials and preparation methods are the same as those in Application Example 1.
[0204] Application Example 5
[0205] A solid-state lithium-ion battery, which differs from Application Example 1 in that the positive electrode material in this example is replaced with lithium cobalt oxide (LCO), and other preparation raw materials and preparation methods are the same as those in Application Example 1.
[0206] In order to study the application performance of PVDF-HFP@TFOMA solid electrolyte membrane in different positive electrode materials, Application Examples 3 to 5 changed the type of positive electrode material on the basis of Application Example 1, and the capacity, rate performance, cycle performance and low temperature performance of the solid-state lithium-ion battery were tested using the test method of Application Example 1.
[0207] The results show that the PVDF-HFP@TFOMA solid electrolyte membrane exhibits a high initial discharge specific capacity and good cycle stability under the high nickel ternary material positive electrode. It can be seen that the solid electrolyte of the embodiment of the present invention can be used to prepare a solid-state lithium-ion battery with excellent performance.
[0208] Fig.11 The charge and discharge specific capacity and coulomb efficiency of the battery in Application Example 3 at different current densities are: Fig.12 The voltage-specific capacity curve of the battery in Application Example 3 at different current densities. The typical charge-discharge characteristic platform reflects the full electrochemical reaction of the positive electrode material. 0.9 Co 0.05 Mn 0.05 When O2 is used as the positive electrode material, the discharge capacity after electrochemical activation is not less than 200 mAh g at current densities of 0.1C, 0.2C, 0.5C, 1C and 2C. -1 、195mAh·g -1 、190mAh·g -1 、180mAh·g -1 and 160mAh g -1 Compared with the good cycle performance and safety of the positive electrode material lithium iron phosphate in Application Example 1, the high-nickel ternary material used as the positive electrode material in Application Example 3 has a higher capacity and energy density, which is conducive to obtaining high-performance battery products.
[0209] Application Example 6
[0210] A solid-state sodium ion battery comprises the following raw materials: (1) positive electrode material: sodium iron phosphate (NVP) or sodium cobalt oxide (NaCoO2); (2) negative electrode material: metal sodium sheet; (3) solid electrolyte: Example 11 uses sodium trifluoromethanesulfonimide (NaTFSI) as the solid electrolyte prepared as the electrolyte salt.
[0211] The preparation method of the solid-state sodium ion battery in this example is different from the battery preparation method in Application Example 1 in that the positive electrode material is replaced with the sodium-based positive electrode material in this example, the negative electrode material is replaced with a metal sodium sheet, and the electrolyte membrane is replaced with the solid electrolyte in Example 6. Other preparation raw materials and preparation steps are the same as those in Application Example 1.
[0212] Application Example 7
[0213] A solid-state potassium ion battery comprises the following raw materials: (1) positive electrode material: potassium iron phosphate (KFePO4) or potassium cobalt oxide (KCoO2); (2) negative electrode material: metal potassium sheet; (3) solid electrolyte: Example 12 uses potassium trifluoromethanesulfonyl imide (KTFSI) as the electrolyte salt to prepare the solid electrolyte.
[0214] The preparation method of the solid-state sodium ion battery in this example is different from the battery preparation method in Application Example 1 in that the positive electrode material is replaced with the potassium-based positive electrode material in this example, the negative electrode material is replaced with a metal potassium sheet, and the electrolyte membrane is replaced with the solid electrolyte in Example 7. Other preparation raw materials and preparation steps are the same as those in Application Example 1.
[0215] Application Example 8
[0216] A solid-state lithium metal soft-pack battery comprises the following preparation materials: (1) positive electrode material: lithium iron phosphate (LiFePO4) or high-nickel ternary material (NCM); (2) negative electrode material: metal lithium sheet; (3) solid electrolyte: PVDF-HFP@TFOMA of Example 1.
[0217] The preparation method of the solid-state lithium metal soft-pack battery in this example is different from that in Application Example 1 in that the assembly and packaging steps of the battery are different. Specifically in this example, the positive electrode, the negative electrode and the electrolyte membrane are stacked, and finally packaged with an aluminum-plastic film to ensure the dryness and vacuum state inside the battery core to prevent decomposition of the electrolyte and oxidation of the positive and negative electrode materials.
[0218] In order to explore the application of solid-state electrolytes in the preparation of different types of solid-state batteries, Application Examples 6 to 8 apply solid-state batteries to the preparation of solid-state sodium-ion batteries and solid-state potassium-ion batteries, and adopt different packaging methods. The capacity, rate performance, cycle performance and low-temperature performance of the solid-state batteries obtained are tested using the test method of Application Example 1.
[0219] The results show that the solid-state batteries of Application Examples 6 to 8 all exhibit excellent electrochemical properties, with good capacity, rate performance, cycle performance and high temperature performance.
[0220] From the above embodiments, application examples and comparative examples, it can be seen that in the embodiments of the present invention, compound I is used to prepare a solid electrolyte, and then a solid-state lithium-ion battery is prepared. Due to the special molecular structure of compound I, the mobility and conductivity of lithium ions are significantly improved, and the growth of lithium dendrites is effectively inhibited. Compared with traditional high-polarity solvents such as N,N-dimethylacetamide (DMF), N-methylpyrrolidone (NMP) or dimethyl sulfoxide (DMSO), compound I (such as N-methoxy-N-methyl-2,2,2-trifluoroacetamide TFOMA) significantly reduces the corrosiveness to lithium metal negative electrode materials and various positive electrode materials, and improves the electrochemical interface stability. In addition, the solid electrolyte of the embodiment of the present invention is particularly suitable for positive electrode materials high nickel ternary materials (such as LiNi 0.9 Co 0.05 Mn 0.05 In addition, the raw materials of compound I (especially TFOMA) are easily available, which has significant cost advantages and industrialization potential.
[0221] The application example of the present invention adopts the solid electrolyte of the embodiment of the present invention as the electrolyte layer, combines lithium iron phosphate or high nickel ternary material (such as NCM91) as the positive electrode, and metal lithium or graphite as the negative electrode, and exhibits excellent electrochemical properties, including: (1) high capacity and high rate performance: especially when matched with high nickel ternary positive electrode material, it exhibits excellent high rate discharge capability; (2) long cycle life: it exhibits excellent capacity retention rate at different rates, which provides the possibility for the development of long-life batteries; (3) improved safety: based on the stability of PVDF-HFP itself and the low polarity characteristics of TFOMA, it can significantly improve the safety performance of the battery.
[0222] The solid electrolyte of the embodiment of the present invention can be used in various solid-state batteries, including but not limited to solid-state lithium-ion batteries, solid-state lithium-sulfur batteries, solid-state sodium-ion batteries, solid-state potassium-ion batteries, solid-state magnesium-ion batteries, solid-state zinc-ion batteries and solid-state aluminum-ion batteries. Due to the low polarity of the TFOMA solvent, it is expected to alleviate the polysulfide shuttle effect and improve the performance of lithium-sulfur batteries; by replacing lithium salts with appropriate sodium salts, TFOMA-based solid electrolytes can be applied to solid-state sodium-ion batteries, providing new material options for large-scale energy storage systems; similarly, after replacing with potassium salts, it can be used to develop solid-state potassium-ion batteries and expand the application scope of new energy storage technologies.
[0223] In summary, the present invention, through the design of the molecular structure, allows compound I to maintain low polarity while introducing a functional group alkoxy group that can weakly coordinate with the electrolyte ions, thereby achieving multiple optimizations of the compound performance. By introducing compound I, the comprehensive performance of the solid electrolyte, including ionic conductivity, electrochemical stability and electrode interface compatibility, can be greatly improved, and it is also beneficial to simplify the preparation process of the solid electrolyte, which provides important technical support for the development of a new generation of high-performance solid electrolytes and solid-state batteries, and is expected to promote the further development of electrochemical energy storage technology.
Claims
1. Use of compound I in preparing a solid electrolyte, characterized in that: The structural formula of compound I is shown below: Wherein, X1, X2, and X3 are each independently selected from hydrogen, fluorine, chlorine, bromine, iodine, hydroxyl, amino or thiol, and X1, X2, and X3 are not hydrogen at the same time, and at most only one of X1, X2, and X3 is a hydroxyl, amino or thiol group; R1 and R2 are each independently selected from substituted or unsubstituted C1~C10 straight or branched alkyl, substituted or unsubstituted C3~C10 cycloalkyl, substituted or unsubstituted C1~C10 siloxane; wherein the substituted substituent includes at least one of fluorine, chlorine, bromine or iodine; the number of substitutions ranges from single substitution to full substitution.
2. The use according to claim 1, characterized in that: Compound I is selected from Compound A shown below:
3. A solvent for preparing a solid electrolyte, characterized in that: The invention comprises the compound I used in claim 1 or 2.
4. A solid electrolyte, characterized in that The preparation method comprises the following raw materials: a polymer, an electrolyte salt, and the solvent according to claim 3; the polymer comprises at least one of a fluorinated polymer, a polyolefin polymer, a polynitrile polymer, a polyether polymer, a polyester polymer, a polyacrylate polymer, a chlorine-containing polymer or a polysiloxane polymer.
5. The solid electrolyte according to claim 4, characterized in that: The electrolyte salt includes at least one of a lithium salt, a sodium salt, a potassium salt, a magnesium salt, a zinc salt or an aluminum salt; preferably, the anion of the electrolyte salt includes at least one of a hexafluorophosphate ion, a bistrifluoromethanesulfonyl imide ion, a bisfluorosulfonyl imide ion, a difluorooxalatoborate ion, a trifluoromethanesulfonate ion, a nitrate ion, a perchlorate ion or a tetrafluoroborate ion; and / or, the mass ratio of the polymer to the solvent is 1:(1-20); And / or, the mass ratio of the polymer to the electrolyte salt is 1:(0.5-5).
6. The solid electrolyte according to claim 4, characterized in that: The preparation raw materials also include metal salts; Preferably, the mass percentage of the metal salt in the preparation raw material is 0.01-10%; and / or the metal salt includes at least one of titanium acetylacetonate, vanadium acetylacetonate, titanium tetrachloride or vanadium chloride.
7. The solid electrolyte according to claim 4, characterized in that: The thickness of the solid electrolyte is 5 to 50 μm; And / or, the ionic conductivity of the solid electrolyte at 30°C is ≥ 2×10 -4 S cm -1 ; And / or, the ionic conductivity of the solid electrolyte at 75°C is ≥ 8×10 -4 S cm -1 ; And / or, the electrochemical stability window of the solid electrolyte is ≥4.3V vs.Li / Li + .
8. A method for preparing a solid electrolyte according to any one of claims 4 to 7, characterized in that: The following steps are involved: The solid electrolyte is obtained by mixing various raw materials, forming a film, and vacuum drying.
9. A solid-state battery, characterized in that: The invention comprises a positive electrode material, a negative electrode material and the solid electrolyte according to any one of claims 4 to 7.
10. The solid-state battery according to claim 9, characterized in that: The positive electrode material includes at least one of lithium iron phosphate, lithium cobalt oxide, high nickel ternary material, sulfur, sodium iron phosphate, sodium cobalt oxide, potassium iron phosphate or potassium cobalt oxide; And / or, the negative electrode material includes at least one of lithium, sodium, potassium, magnesium, zinc or aluminum.
Citation Information
Cited By
Silicon-carbon composite negative electrode material, preparation method thereof and secondary battery
CN120978036A
Silicon-carbon composite negative electrode material, preparation method thereof and secondary battery
CN120978036B